2016
DOI: 10.1038/srep22486
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to Mycobacterial heat shock protein 70 accompany self-reactivity to human BiP in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease, and a member of human heat shock protein (HSP) 70 protein family, Binding Immunoglobulin Protein (BiP), has been identified as an important autoantigen for T and B cells. We herein focused on Mycobacterial (Myc) HSPs and immune responses to MycHSPs in RA patients. Serum titers of antibodies against MycHSP70 were significantly elevated in RA patients and correlated with serum anti-BiP antibody titers. A MycHSP70-derived HLA-DR4 major epitope was identified usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Autoimmune response to Mycobacterial (Myc) HSP70 and human binding immunoglobulin protein (Bip), a member of the human HSP70 family, has also been reported in RA patients [ 102 ]. Shoda’s study showed that the similarity between Myc HSP70 287–306 and human Bip 336–355 epitopes can lead to a broken immune tolerance, triggering an auto-immune response as a result of the T cells’ inability to distinguish between self- and pathogens’ antigens [ 103 ] ( Figure 1 ).…”
Section: The Role Of Mycobacterial Infections In Rheumatoid Arthrimentioning
confidence: 99%
“…Autoimmune response to Mycobacterial (Myc) HSP70 and human binding immunoglobulin protein (Bip), a member of the human HSP70 family, has also been reported in RA patients [ 102 ]. Shoda’s study showed that the similarity between Myc HSP70 287–306 and human Bip 336–355 epitopes can lead to a broken immune tolerance, triggering an auto-immune response as a result of the T cells’ inability to distinguish between self- and pathogens’ antigens [ 103 ] ( Figure 1 ).…”
Section: The Role Of Mycobacterial Infections In Rheumatoid Arthrimentioning
confidence: 99%
“…Immunization of HLA-DR4 transgenic mice with HSP70 287−306 derived from Mycobacterium leporae induced the development of BiP autoantibodies. In the collagen-induced arthritis model, oral administration of this mycobacterial peptide induced tolerance, blunting the development of arthritis and reducing anti-BiP autoantibody production (132). Thus, tolerance against BiP, a common autoantigen in RA and JIA, may be broken by immune responses directed against a mycobacterial pathogen.…”
Section: Autoantibodies and Potential Examples Of Molecular Mimicry Imentioning
confidence: 99%
“…Some Hsps have been reported to play important roles in antigen presentation and maturation of dendritic cells [ 9 , 10 ]. Recently, many studies have showed that Hsps from parasites [ 11 , 12 ] or bacteria [ 13 ] exhibited potent immunogenicity and induced protective immunity against specific infections, thus these proteins have become momentous target proteins in vaccine development against various infections. Heat shock protein-70 of Trichinella spiralis ( Ts -Hsp70) is a member of Hsp70 family with molecular weight of about 70 kDa and an immunodominant antigen during infection.…”
Section: Introductionmentioning
confidence: 99%